Eponyms related to genetic disorders associated with gingival enlargement; part II - Nora Mohammed Al-Aboud; Hanan Barnawi; Ahlam Al Hakami (Our Dermatology Online, 2015)
There are genetic disorders associated with gingival enlargement. In our part I, we reviewed the eponyms linked to Hereditary Gingival Fibromatosis (HGF) [1]. Historical Article How to cite this article: Al Aboud A, Al-Aboud NM, Barnawi H, Al Hakami A. Eponyms related to genetic disorders associated with gingival enlargement: Part II. Our Dermatol Online. 2015;6(1):114-117. Submission: 27.05.2013; Acceptance: 21.09.2014 DOI: 10.7241/ourd.20151.32 In this part II of this review, we are going to shed some light on eponyms linked to groups of genetic disorders which may feature gingival enlargement.